PENGARUH AUDIT SEKTOR PUBLIK, KOMPETENSI APARATUR PEMERINTAH DAERAH, PROFESIONALISME APARAT PENGAWASAN INTERN PEMERINTAH TERHADAP PENERAPAN GOOD GOVERNMENT GOVERNANCE (GGG) SERTA IMPLIKASINYA PADA AKUNTABILITAS KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) - Leny Nofianti (Indonesian Journal of Economics and Business, 2012)
The research was intended to examine: 1) the influence of implementation of the public sector audit, the competence of local government Apparatus and the Professionalism Of Internal Functional Controlling Agency toward implementation Good Government Governance/GGG. 2) the influence of implementation of the public sector audit, the competence of local government Apparatus and the Professionalism Of Internal Functional Controlling Agency toward performance of Local government accountability. 3) the influence of application of Good Government Governance/GGG toward Local Governmentperformance accountability. The research methods used in this research was the explanatory research. Sampling techniquesused was Proportionate Stratified Cluster Random Sampling. The samples obtained in this research was 57 Local Government Unit Agencies (SKPD). The primary data were collected by questionaires, the Reports of the Evaluation (LHE) on Performance Accountability in The Unit Of Local Infrastructure Of Riau Province were used for secondary data. Validity and reliability of the questionnaire was tested first before testing hypotheses was performed. The analysis technique used in this research was a Structural Equation Modelling (SEM) or variance-based component that was made famous by Partial Least Squares (PLS). Based on the results of data analysis and discussion, it was obtained the following research findings: 1) The significance level of 5% can be inferred implementation of the public sector audit, the competence of local government Apparatus and the Professionalism Of Internal Functional Controlling Agency significantly effect to the implementation of Good Government Governance/GGG. 2)The significance level of 5% can be inferred implementation of the public sector audit, the competence of local government Apparatus and the Professionalism Of Internal Functional Controlling Agency significantly effect to the Local Government accountability performance significantly. 3) The significance level of 5% can be inferred application of Good Government Governance/GGG significantly effect to the Local Government accountability performance.